Occurrence of Enteric Parasites in Sheep (Ovis aries) from Gabtoli Livestock Market, Dhaka, Bangladesh - Hamida Khanum; Sharmin Musa; Halima Khatun; Priyanka Barua; Mandira Mukutmoni; Romana Akter (Contemporary Research and Perspectives in Biological Science Vol. 1, 2024)
Enteric parasitic infection in small ruminants is a problem in commercial production systems as it has a huge influence on growth and related costs of control trials. Heavy infections with helminths lower the immunity of the animals. The present study was conducted to determine the prevalence of enteric parasites in sheep (Ovis aries). A total of 96 ((40 male sheep and 56 female sheep) stool samples were collected from Gabtoli cattle market, Dhaka from April to November 2017. The Formol Ether Concentration technique was applied to process the stool samples. Balantidium sp. (41.67%; CPG 17.5±3) followed by Entamoeba sp. (37.50%; CPG 7.22±3) showed the maximum prevalence among protozoan parasites. Fasciola sp. (45.83%; EPG 45±5) and Hymenolepis nana (37.50%, EPG 17.22±7.5) were the most prevalent among trematodes and cestodes, respectively. Ostertagia sp. (50%; EPG 26.9±5) showed the uppermost prevalence among the nematodes. Trichiurisovis showed the highest intensity (53.7±13.5) followed by Strongyloides sp. (49.8±14). Giardia sp. had the lowest prevalence (8.33%; CPG 6±0.5). All sheep species were nearly equally affected, with the exception of protozoans and cestodes. In order to develop effective control measures, further work is required for a thorough examination and monitoring of intestinal parasites in small ruminants. Proper control measures are indispensable to generate defence against economic damage regarding livestock production and management and to minimise the deadly effect of parasites on animal health. Additional studies with large sample sizes can depict the definite prevalence of enteric parasites. Routine therapy reduces this burden but small strategies are needed to limit the onset of drug resistance.